Brackenridge's Medical Selection of Life Risks
eReference.
Keywords: The fifth edition of this leading reference book on insurance medicine, provides a comprehensive guide to life expectancy for underwriters and clinicians involved in the life insurance industry. Extensively revised and expanded, the new edition reflects developments in life and healthcare insurance as well as medicine.